Restructuring Corporate Income Tax and Value Added Tax in Vietnam : An Analysis of Current Changes and Agenda for the Future - World Bank (Washington, DC, 2014)
The study is in two parts, part one covering the various policy aspects of Corporate Income Tax (CIT) and includes issues such as expenses and deductions to determine the tax base, transfer pricing, thin capitalization, taxation of special entities, and tax incentives. All this is done in the backdrop of international experience of corporate income taxes applied globally. Finally, alternatives for rate rationalization and their impact on CIT revenues using a forecasting model are examined. The existing provisions of the law are referenced in this part of the study as well, and further scope for reform discussed as necessary. Part two of the study presents a similar analysis of value added tax as well as forecasting of VAT revenues. This chapter examines the present rate structure including zero-rating, exemptions and exclusions from VAT, and VAT refunds. Taxation of some special sectors such as agriculture, real estate and exports is also analyzed. All this is again done in the milieu of international experience of value added taxes in Organization for Economic Co-operation and Development (OECD) countries, Brazil, Russia, India, China and South Africa (BRICS) countries and the countries of ASEAN so as to get a practical and realistic picture. Finally, a revenue forecasting model for VAT is presented with a guideline for estimating VAT threshold for exempting small traders. All the chapters make reference to the present provisions in law and also the way forward to further strengthen and streamline the VAT.